The Impact of Media in the Disruption Era as a Realization of 2019 Presidential Election Integration - Saputri, Wahyuningtyas Dwi; Resty, Dian Riskiana (Law Research Review Quarterly, 2018)
As time goes by the needs of life in the community also increase driven by the demands of the times that are increasingly modern. This makes the community to keep abreast of the development of the era in order to fulfill their needs. Fulfillment of needs that are felt to be increasingly complex which ultimately leads to a time when technology or digital media get a major place in the life of society, especially the Indonesian people. This is not new anymore because the number of Indonesian internet users is around 143.26 million based on a survey by the Indonesian Internet Service Users Association (APJII) in 2017. Emerging technologies and media can help in people's lives in various fields. But with the evolution of this technology it should be interpreted as a matter of uniting the needs of the community even though there are many threats that can occur. The role of the media is very quickly entered into the scope of society. Like in the economic, political and socio-cultural spheres. The negative impact itself from this technology is the difficulty of integration in society because the information that comes in is very diverse so this can affect the mindset of the community. Reflected at this time the 2019 presidential election will be held. This media function is also expected to be a positive bridge for the community.